Strategi Kebijakan Reforma Agraria dalam Mewujudkan Kesejahteraan Masyarakat yang Berkeadilan Sosial dengan Berasaskan Konstitusi - Habib Ferian Fajar; Julfahmi Syahputra; Mareta Puri Nur Ayu Ningsih (Jurnal Hukum Lex Generalis, 2022)
Agrarian conflicts are still a legal problem in Indonesia. The presence of a strategy in the form of agrarian reform is expected to be able to make a real contribution to realizing social justice and people's prosperity for all Indonesian people. The implementation of agrarian reform is marked by a comprehensive arrangement of assets and access arrangements, so it is important to carry out a thorough evaluation of justice and community empowerment. The results obtained from this study indicate that the organizers of agrarian reform are expected to be able to ensure an increase in community welfare and realize social justice, either through the efforts of the Agrarian Reform Task Force (GTRA) or the Government which carries out a compromise strategy with ministries/agencies to ensure land rights through agrarian reform.